Biocontrol activity and action mechanism of Bacillus velezensis strain SDTB038 against Fusarium crown and root rot of tomato - Chen, Qiqi; Qiu, Yue; Yuan, Yazhen; Wang, Kaiyun; Wang, Hongyan (Frontiers in Microbiology, 2022)
Fusarium crown and root rot of tomato is a soilborne diseases that has brought serious harm and economic losses to tomato production in facilities in recent years. The disease has been reported in more than 30 countries worldwide, but there are few reports on its biological control. A Bacillus velezensis strain SDTB038 with biocontrol effects was isolated and identified in a previous study and is considered one of the most important PGPRs. Here, tests showed that B. velezensis SDTB038 could promote healthy growth of tomatoes, and the treatment effect at the 108 CFU/mL SDTB038 concentration was the most obvious. Meanwhile, control effect of 108 CFU/mL SDTB038 bacterial concentration on Fusarium crown and root rot of tomato was 42.98% in the field. Seven secondary metabolite biosynthesis gene clusters were found in strain SDTB038 by whole genome sequencing, explaining its biocontrol effects. Studies have shown that bacterial concentrations of SDTB038 at different concentrations had a negative influence on the mycelial growth of Fusarium oxysporum f. sp. radicis-lycopersici (FORL). Strain SDTB038 could generate indole acetic acid, reduce the reactive oxygen species conments in plants at low temperature, promote the rapid recovery of plants at low temperature, and increase the expression of genes involved in cold temperature resistances. In summary, the strain B. velezensis SDTB038 may be a promising bacterial agent for biological control of Fusarium crown and root rot of tomato, and an important source of potential antimicrobial compounds.